Comportamiento de la neología en tiempos de coronavirus - Luna García, Rosa (2022)
The main objective of this mixed research was to analyze the characteristics of the stylistic and denominative neologisms coined in the context of the coronavirus disease. For this purpose, the researcher worked with a corpus made up of 831 coronavirus neologisms extracted from Hispanic journalistic sources, dictionaries on covid-19 and neology observatories. The results obtained allowed the following conclusions to be drawn: The coronavirus neology has a high percentage of expressive neologisms with great thematic dispersion. Neologisms based on total or partial acronyms were the privileged resource in the coining of expressive coronavirus neologisms. The systematic instability of the coronavirus neology was reflected in the considerable denominative variation existing in the two types of neology, in the variety of methods for coining neologisms used for the same referent and in the different thematic nodes in which these variants appear.